Agroforestry: Opportunities and Challenges in Timor-Leste - Paudel, S.; Baral, H.; Rojario, A.; Bhatta, K.P.; Artati, Y. (MDPI, 2022)
Agro forestry is a land management system that integrates trees, agriculture crops, and animal farming in order to provide a diverse range of ecosystem services. Timor-Leste, the newest country and one of the least developed counties, has faced multidimensional challenges on land use management, including deforestation, land degradation, and poverty. The agroforestry system is recognized as one of the viable options for balancing the socio-economic needs and ecological functions of the lands in Timor-Leste. The system has been practiced traditionally by farmers in the country; however, the lack of knowledge and experience, limited institutional capacity, and lack of funding have impeded the wider implantation of the agroforestry system in Timor-Leste. The Strategic Development Plan of Timor-Leste has recommended sustainable agriculture and natural resources management in the rural areas of the country to generate income and create employment for the youths. The paper presents the initiatives, challenges, and opportunities of agroforestry application in Timor-Leste to support sustainable forest management and livelihood improvement. Learning from existing initiatives, capacity building, market access, and financial incentives could promote the agroforestry system in the country.